1997
DOI: 10.1037/0022-0167.44.3.284
|View full text |Cite
|
Sign up to set email alerts
|

Supervisee multicultural case conceptualization ability and self-reported multicultural competence as functions of supervisee racial identity and supervisor focus.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
193
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(209 citation statements)
references
References 47 publications
12
193
2
1
Order By: Relevance
“…For instance, supervisees reported increases in personal awareness of cultural issues (Toporek et al, 2004), in their ability to include multicultural issues in client treatment conceptualization (Ladany, Inman, Constantine, & Hofheinz, 1997), and in overall case conceptualization abilities (Gainor & Constantine, 2002) when multicultural issues were addressed in supervision in comparison to when they were not addressed. Furthermore, supervisees also reported acquiring higher levels of multicultural competence when multicultural issues were addressed as opposed to when they were not addressed (Constantine, 2001).…”
Section: Research On Cross-cultural Supervisionmentioning
confidence: 99%
“…For instance, supervisees reported increases in personal awareness of cultural issues (Toporek et al, 2004), in their ability to include multicultural issues in client treatment conceptualization (Ladany, Inman, Constantine, & Hofheinz, 1997), and in overall case conceptualization abilities (Gainor & Constantine, 2002) when multicultural issues were addressed in supervision in comparison to when they were not addressed. Furthermore, supervisees also reported acquiring higher levels of multicultural competence when multicultural issues were addressed as opposed to when they were not addressed (Constantine, 2001).…”
Section: Research On Cross-cultural Supervisionmentioning
confidence: 99%
“…Findings indicated that, controlling for social desirability, there was no significant relationship between each of the four self-report multicultural counseling competence instruments and multicultural case conceptualization ability, supporting previous similar findings by Ladany, Inman, Constantine, and Hofheinz (1997). The authors suggested that these findings reflected the likelihood that instruments intended to measure multicultural counseling competence may have measured anticipated rather than actual attitudes or beliefs, knowledge, and skills, or that they, in fact, were measuring multicultural counseling self-efficacy rather than multicultural counseling competence.…”
Section: Multicultural Counseling Competencesupporting
confidence: 80%
“…Research has shown that self-ratings on multicultural competence scales do not correlate with observer measures of cultural competence (Worthington et al, 2000) or with multicultural case conceptualization ability (Constantine & Ladany, 2000;Ladany et al, 1997). Although minimal research has been done in this area, self-report measures have not been found to correlate with any other measures of multicultural counseling competence currently available, indicating that the constructs assessed through these measures differ by respondent.…”
Section: Both the CCI And The Cbmcs Have Been Influenced By The Apa'smentioning
confidence: 92%
“…Indeed, findings suggest no statistically significant relation between self-reported multicultural competence and written multicultural case conceptualization ability, a measure of demonstrated multicultural competence (Constantine & Ladany, 2000;Ladany et al, 1997) or observer ratings of multicultural competence (Worthington, Mobley, Franks, & Tan, 2000). Such concerns have raised questions about the completeness and accuracy of current models and have led to suggestions that client input may also play an important role in furthering understanding of multicultural counseling competence (Fuertes et al, 2001;Pope-Davis et al, 2001 Cultural Sensitivity), factor analysis suggests that it measures only one factor (LaFramboise et al, 1991).…”
Section: Measuring Cultural Competencementioning
confidence: 99%
See 1 more Smart Citation